O curso técnico em guia de turismo na faculdade SENAC Porto Alegre/RS (2012 – 2015) - Abreu, Carina Vasconcellos (2015)
Tourist guide is the professional in charge of leading, orienting and supporting individual tourists or tourist groups during their traveling. This profession was regulated in 1993, and since 2001 technical training is mandatory for its practice. Even though, to the present moment this course has not been thoroughly researched. So the general objective of this research is to analyze the tourist guide training, starting from a case study about a unit of the Serviço Nacional de Aprendizagem Comercial – SENAC (National Service for Commercial Learning), which pioneered in this training in Brazil. Therefore the Course Plan effective from 2012 to 2015 for the technical course on Tourist Guide offered by Faculdade Senac Porto Alegre (Senac Porto Alegre College) was selected as the object to this study. The first specific objective here is to present the context in which the tourist guide profession and its training in Brazil on several levels were regulated. The second objective was to analyze profiles from tourist guides registered in the State of Rio Grande do Sul and their perceptions about their training and entry in the local market, in order to establish an analysis context. Data collection, which reached 117 respondents, allowed us to register that most guides work as free lancers and get updated by doing their own research. Also, they give priority to language courses. A growing profession is noticed, considering that most respondents finished their courses in the last five years. In what concerns these professionals’ entry in the labor market, almost 70% of respondents registered a positive entry, which points out that there is a demand for professionals. The curriculum demanded by Brazilian law, established by Normative Act N. 427, which dates from 2001 and establishes the course outlines and its details, was also analyzed, as compared to the Course Plan studied. They both reflect restrains already seen in the profession regulation, showing both difficulties in describing the tourist guide competences, and a need for updating and redirecting. In what concerns the former students from the Course Plan studied here, 27.7% of a total of 36 former students were asked. In overall these former students are similar in their profiles and entry in the market as compared to their colleagues from other courses in this State. Analyzing their perceptions about the competence acquisition for their work based on the competences foreseen in the studied Course Plan, the former students from the studied institution see themselves as better prepared than their colleagues from other institutions. This shows that this course stands out as compared to other choices offered in the local market, also in what concerns fluency in foreign languages, which is a shortage discussed at several points of this research. This analysis allows us to point out skills that would improve the development of the curriculum, such as the competence related to research in several means, with a critical ability to select relevant information; competence in cultural mediation; interpersonal development; entrepreneurship; besides the use of technical travels as learning situations that gather all elements from several lectures.